PENGELOLAAN BARANG MILIK NEGARA : IMPLEMENTASI PENATAUSAHAAN BARANG MILIK NEGARA DI UNIVERSITAS GADJAH MADA - , NURWAHID, S.KOM ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesian Government Regulation No. 153 of 2000 on the establishment of the University of Gadjah Mada (GMU) as a state-owned entity (PT BHMN), making special autonomy for GMU includes academic and financial autonomy. GMU still receive funding from the government should be held accountable according to Government Regulation No. 6 of 2006 , concerning the administration of State Asset. Government Regulation No. 17 and No. 66 of 2010 on the Management and Operation of Education, which also includes the cancellation the status of PT BHMN. This research is motivated by